Meningkatkan Hubungan Sosial Antar Teman Melalui Layanan Bimbingan Kelompok Dengan Teknik Permainan Edukatif Toples Rahasia Pertemanan Pada Peserta Didik KELAS X-9 SMAN 3 KEDIRI - Henida Nuha Nafisa; Rosa Imani Khan; Devi Asmirandra Milasanty (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This classroom action research in guidance and counseling aims to improve students’ social relationship skills through group counseling services using the educational game technique Toples Rahasia Pertemanan (The Secret Friendship Jar). The study was conducted in class X-9 of SMA Negeri 3 Kediri over two cycles, which included planning, implementation, observation, and reflection stages. The pre-cycle results showed that most students had low levels of social relationship skills. In the post-test of Cycle I, 4 out of 6 students (66.7%) were in the medium category, while 2 students (33.3%) were still in the low category. After improving the strategy in Cycle II, the post-test results showed that all students (100%) reached the medium category. This means there was a 33.3% improvement, proving that group counseling using the Secret Friendship Jar game can create a fun and interactive atmosphere, increase student participation, and effectively improve their social relationship skills with peers.